2014
DOI: 10.1002/chem.201402010
|View full text |Cite
|
Sign up to set email alerts
|

(Dibenzoylmethanato)boron Difluoride Derivatives Containing Triphenylamine Moieties: A New Type of Electron‐Donor/π‐Acceptor System for Dye‐Sensitized Solar Cells

Abstract: (Dibenzoylmethanato)boron difluoride derivatives containing triphenylamine moieties were synthesized as a new type of electron-donor/π-acceptor system. These new compounds exhibited long-wavelength absorptions in the UV/Vis spectra, and reversible oxidation and reduction waves in cyclic voltammetry experiments. Their amphoteric redox properties are based on their resonance hybrid forms, in which a positive charge is delocalized on the triphenylamine moieties and a negative charge is localized on the boron atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 100 publications
2
15
0
Order By: Relevance
“…Among the substancesi nt his family,d ibenzoylmethanatoborond ifluoride (P1 BF 2 ,S cheme 1) is an especially interesting compound from the viewpoint of probing relationshipsb etween aggregation mode and FL properties. [23][24][25][26][27][28][29][30][31][32][33][34][35] Since the report by Mirochnik and co-workers showing that P1 BF 2 FL involves emission from arrays of molecules in crystalsi nw hich intermolecularo rbital interactions occur, [30][31][32][33][34][35] many others have observed that P1 BF 2 derivatives exhibit interesting molecular aggregation-based emissionp henomena such as mechanofluorochromism, [36][37][38][39] aggregation-induced emission (AIE), [40] and room-temperature phosphorescence. [41,42] Guided by thesee arlier efforts, we carriedo ut an investigation aimed at elucidating the FL properties and crystal-packing structures of 1BF 2 derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Among the substancesi nt his family,d ibenzoylmethanatoborond ifluoride (P1 BF 2 ,S cheme 1) is an especially interesting compound from the viewpoint of probing relationshipsb etween aggregation mode and FL properties. [23][24][25][26][27][28][29][30][31][32][33][34][35] Since the report by Mirochnik and co-workers showing that P1 BF 2 FL involves emission from arrays of molecules in crystalsi nw hich intermolecularo rbital interactions occur, [30][31][32][33][34][35] many others have observed that P1 BF 2 derivatives exhibit interesting molecular aggregation-based emissionp henomena such as mechanofluorochromism, [36][37][38][39] aggregation-induced emission (AIE), [40] and room-temperature phosphorescence. [41,42] Guided by thesee arlier efforts, we carriedo ut an investigation aimed at elucidating the FL properties and crystal-packing structures of 1BF 2 derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…The quantum yields of piperidyl‐substituted phenyl systems 5 and 6 in CH 2 Cl 2 are about 1.0 % and 2.8 % respectively. The low quantum yields of 5 and 6 are presumably correlated to strong CT character in the transition, which permits large, energy‐dissipating nuclear reorganization …”
Section: Resultsmentioning
confidence: 99%
“…One of the main shortcomings of metal complex dyes is their weak absorption in the red region of visible spectrum. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] In our earlier report, we have designed a different pyridomethene-BF 2 complex, with a similar structure to BODIPY, that exhibited a very large extinction coefficient (ε>5×10 4 M -1 cm -1 ). A high absorption coefficient in the visible wavelength will increase the value of shortcircuit current density (J sc ).…”
Section: Introductionmentioning
confidence: 99%